Commuters Preferences and Their Willingness to Pay for Modern Public Utility Vehicle (MPUV) - Lalio, Ivy; Navarro, Gladys (Bina Nusantara University, 2025)
The study aims to determine the commuter’s preferences and predicts the commuters' Willingness to Pay (WTP) for Modern Public Utility Vehicle (MPUV). The satisfaction and importance of the commuters’ preferences are essential in determining the attitude of commuters, particularly in what the commuters value in terms of comfort and convenience. Personal factors such as gender, classification, satisfaction, and importance level were considered and economic factors such as the monthly household income and transportation expenses of the respondents are included as determinants of their willingness to pay for additional MPUV. The study utilizes descriptive and a quantitative approach or Binary Logistic Regression (BLR) Model. While a tool validated structured questionnaire based on the Contingent Valuation Method (CVM) were used. There were 324 respondents from the two proximate private and public schools in senior high level. The result shows that the overall satisfaction level of commuters with traditional PUVs was just right and are mostly dissatisfied with the factors on environment-friendly and safe or security features of traditional PUVs. Using BLR, the willingness to pay for additional PUV was determined the personal and economic predicting a positive chance that the commuters are willing to pay for Modern PUV, however, these indicators are not significant. Conversely, two indicators yield a significant relationship with the willingness to pay. First is the amount willing to pay and second is the overall level of importance by the commuters. The results assist to improve the transportation infrastructure, services and recommend a market-driven policy matrix.